Treaty, let's get it right! : frequently asked questions. - Australia. Aboriginal and Torres Strait Islander Commission (Woden, A.C.T. : Aboriginal and Torres Strait Islander Commission, 2001)
Answers some of the questions people have about a treaty between Indigenous and non-Indigenous Australians such as - What is a treaty?; Why should there be one; Would there be only one treaty; What would be in a treaty? What would the legal status of a treaty be? How will Indigenous people be consulted about a treaty? Will a treaty be socially divisive; and other questions.
Cover title.
"www.treatynow.org".
"May 2001" --Back cover.
Keywords: Aboriginal Australians -- Treaties; Aboriginal Australians -- Land tenure; Aboriginal Australians -- Civil rights; Aboriginal Australians -- Politics and government; Aboriginal Australians -- Government relations; Law - Constitutional law - Treaty movement; Australia